ANALYTICAL METHOD DEVELOPMENT & VALIDATION OF ETRAVIRINE IN ITS BULK DOSAGE FORM BY USING RP-HPLC METHOD AS PER ICH GUIDELINES - Ghosh, Somsubhra; A, Sailaja; Bvv, Ravikumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: An accurate, precise, rapid and economical reverse phase high performance liquid chromatography (HPLC) method has been developed and validated for the estimation of etravirine in pharmaceutical dosage forms, using an ultraviolet detector. Method: Elution was carried out using a mobile phase consisting of HPLC grade acetonitrile and flow rate was set on 1 ml/minute at 271 nm wave length. The retention time for etravirine was found to be 1.80 minutes. Result: The method was found to be linear in the range of 10-60 Î¼g/ml. In the linearity study, regression equation and correlation coefficient were found to be y=16.95x+17.148 and 0.999, respectively. This method was rugged and robust in different testing criteria, limit of detection and limit of quantification was found to be 0.514 Î¼g/ml and 1.713 Î¼g/ml respectively. Accuracy study was carried out in three different concentration level i.e. 50, 100, 150% and % recovery of the method was found to be 98.6%, 99.08%, 99.17% respectively in three different levels and mean recovery was 98.95% and hence method was accurate. Conclusion: Results of all validation parameter were within the limits as per International Conference on Harmonization guideline. Keywords: High performance liquid chromatography, Validation, Method development, Artemether, Accuracy, Precision.